Problems in Teaching English Tenses to Students of PGSD UNNES - Widagdo, Arif (Elementary School Teacher, 2018)
This study focused on the problems in teaching tenses to Primary School Teacher Education Department (PGSD), Faculty of Education, Semarang State University (UNNES). There were some of the problematic and confusing tenses such assimple tense and present perfect tense, present continuous and present simple, past simple and past continuous tense. This research used qualitative approach. It was conducted in PGSD Department, Faculty of Education, Semarang StateUniversity in 2015 by involving 120 students as the samples. The researcher used questionnaire, interview sheet, and test items as the instruments. The data were analyzed by using descriptive method. Besides that teaching grammar had been handled throughout this study with the data obtained from the written exams of the learners. Most frequently occurred errors were listed and they were analyzed in details. The findings revealed that the reasons for these errors mostly derived from mother tongue interference and lacked of adequate linguistic background. The other component of this article was to offer remedial teaching activities for foreign language learners to compensate the shortcomings.